Aid for Russian Families with Children: Assessment of Demographic Effectiveness. Issue 2 (3rd March 2016) - Arkhangel'skii, V.N.
Abstract : This article presents the results of a sociological survey conducted in 2013 in order to assess the effectiveness of demographic policy measures. We show that the most effective measures were federal maternal (family) capital, the increase in benefits for families with children up to 1.5 years of age, regional maternal capital, and land allocation for families with three or more children. The assessments of aid measures depend on how many children the family has.